Efficient preparation of Ni-M (M = Fe, Co, Mo) bimetallic oxides layer on Ni nanorod arrays for electrocatalytic oxygen evolution. (December 2021) - Yan, Yong; Liu, Haocen; Liu, Chunyue; Zhao, Yuguo; Liu, Shuzhen; Wang, Dong; Fritz, Mathias; Ispas, Adriana; Bund, Andreas; Schaaf, Peter; Wang, Xiayan
Highlights: An efficient method was developed for preparing Ni-based nanorod arrays (NRAs). Ni/Ni-M (M = Fe, Co, Mo) bimetallic oxides core/shell structure were fabricated. NRAs structure induces the superior electrochemically active surface area (ECSA). Ni/Ni-Fe NRAs demonstrated both enhanced activity and durability towards OER. Ni-Co and Ni-Mo bimetallic oxides interface are active but unstable towards OER. Abstract: Fabrication of economic and high-performance electrodes for electrocatalytic oxygen evolution reaction (OER) accounts for a crucial issue associated with developing powerful and practical water splitting systems. In this work, free-standing Ni/Ni-M (M = Fe, Co, Mo) bimetallic oxides core/shell nanorod arrays (Ni/Ni-M NRAs) were prepared through electroless deposition of transition metal species on black nickel sheet (nickel nanorod arrays (Ni NRAs)) followed by electrochemical oxidation. All three types of Ni/Ni-M NRAs demonstrated enhanced electrocatalytic activity toward oxygen evolution reactions (OER). Especially, Ni/Ni-Fe NRAs electrode exhibit small onset potential of 1.535 V at current density of 10 mA∙cm −2 . In contrast, the OER durability of these three samples was distinct. At 500 mV constant overpotential, the current density loss in OER of Ni/Ni-Fe NRAs was merely 13.5% for a period of 20000 s; but Ni/Ni-Mo and Ni/Ni-Co NRAs had almost disappeared catalytic activity under the identical conditions. According to many reports, the results were different for the superior OER stability of Ni-based bimetallic catalysts. Electrochemical analysis revealed that the NRAs structure dramatically improves charge transfer efficiency and electrochemically active surface area (ECSA). The present study might provide a new insight to design and fabricate more practical and high-performance Ni-based electrodes for OER. Graphical abstract: Image, graphical abstract